Phase II study of gemcitabine and oxaliplatin in patients with recurrent ovarian cancer: an Australian and New Zealand Gynaecological Oncology Group study. Issue 2 (1st February 2007) - Harnett, P.; Buck, M.; Beale, P.; Goldrick, A.; Allan, S.; Fitzharris, B.; De Souza, P.; Links, M.; Kalimi, G.; Davies, T.; Stuart-Harris, R.
Abstract : Gemcitabine and oxaliplatin have shown single-agent activity in relapsed ovarian cancer. This combination was used to determine response rates, time-to-event efficacy measures, and toxicity in patients with recurrent ovarian cancer. Patients with prior platinum-based chemotherapy who had measurable lesions and/or elevated CA-125 levels were identified as group A (platinum-refractory/platinum-resistant patients) and group B (platinum-sensitive patients). All patients received gemcitabine 1000 mg/m 2 on days 1 and 8 and oxaliplatin 130 mg/m 2 on day 8 every 21 days for up to eight cycles. Seventy-five patients (21 in group A and 54 in group B), with a median age of 58 years (range, 37–78), were enrolled. A median of six cycles (range, 1–8) was administered. By intent-to-treat analysis, 15 patients with measurable disease achieved partial response for an overall best response rate of 20.0% (9.5% in group A and 24.1% in group B). CA-125 response was observed in 48.4% patients (30.0% in group A and 57.1% in group B). Median time to progressive disease was 7.1 months (95% CI, 5.6–9.0 months) with 5.0 months in group A and 8.3 months in group B. Median overall survival was 17.8 months (95% CI, 12.9–21.3 months) with 9.2 months for group A and 20.0 months for group B. Major grade 3/4 toxicities were neutropenia (61.3%), leukopenia (24.0%), nausea (16.0%), and vomiting (22.7%). We conclude that the combination of oxaliplatin and gemcitabine is active in patients with recurrent ovarian cancer, but the regimen is unsatisfactory for further study due to modest response and relatively high toxicity.